Gender bias in sports medicine: an international assessment of sports medicine physicians` perceptions of their interactions with athletes, coaches, athletic trainers and other physicians - Tsukahara, Y.; Novak, M.; Takei, S.; Asif, I. M.; Yamasawa, F.; Torii, S.; Akama, T.; Matsumoto, H.; Day, C. (British Journal of Sports Medicine, 2022)
Objectives: To evaluate the difference between female and male sports medicine physicians regarding disrespectful attitudes and sexual harassment perceived from athletes, coaches, physicians, athletic trainers (ATs) and organisations/administrations.Methods and study design anonymous survey was distributed to sports medicine physicians practicing in 51 countries. X² analysis was used to detect differences between female and male sports medicine physicians and logistic regression analysis was used to determine the independent variables that affect disrespectful attitudes and sexual harassment from sports participants. Results: 1193 sports medicine physicians (31.9% female) participated from 51 countries. The survey revealed that female physicians, compared with male physicians, perceive significantly more disrespect or have their judgement questioned more by the following categories: male and female athletes, male and female coaches, female physicians with more years of experience, male physicians (regardless of years of experience), male and female ATs and organisation/administrations (all <0.05). The only category where the frequency of disrespect was perceived equally by male and female physicians was during their interactions with female physicians who have the same or lesser years of experience. Female sports medicine physicians noted more sexual harassment than male physicians during interactions with male athletes, coaches, ATs and physicians (all <0.001). In the logistic regression, gender was a related factor for perceiving disrespect, especially from male coaches (OR=2.01) and physicians with more years of experience (OR=2.18). Conclusions: Female sports medicine physicians around the world experience disrespectful attitudes, questioning of their judgement and are sexually harassed significantly more often than male counterparts.